Dependability Analysis in the Ambient Assisted Living Domain: An Exploratory Case Study - Rodrigues, Genaina Nunes; Alves, Vander; Franklin, Renato; Laranjeira, Luiz (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
Ambient Assisted Living (AAL) investigates the development of systems involving the use of different types of sensors, which monitor activities and vital signs of lonely elderly people in order to detect emergency situations or deviations from desirable medical patterns. Differently from the state-of-the-art of 'push-buttons', AAL solutions need to provide high accuracy and proactive responses, 'perceiving' lonely elderly people in their household environment through various sensors and carrying out appropriate actions under the control of the underlying software. Dependability in the AAL domain is a critical requirement, since poor system availability, reliability, safety, or integrity may cause inappropriate emergency assistance to potentially have fatal consequences. Nevertheless, contemporary research has not focused on assessing dependability in this domain. Therefore, this work aims at exploring the application of modern quantitative and qualitative dependability analysis techniques based on software architecture. The benefits of using these techniques are twofold. Firstly, they allow us to seamlessly integrate the analysis during subsequent software lifecycle stages in critical scenarios. Secondly, we aim to identify the components which have the highest impact on software system dependability, and therefore, be able to address software architecture and individual software component problems before they are implemented and critical errors occur.